2019
DOI: 10.1007/s00405-019-05347-2
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral trial vocal fold injection with hyaluronic acid in patients with vocal fold atrophy with or without sulcus

Abstract: Purpose To evaluate the outcome of bilateral trial vocal fold injection (VFI) with hyaluronic acid in patients with vocal fold atrophy ± sulcus and to assess the predictive value of trial VFI on the outcome of durable medialization procedure. Methods Voice data collected according to a standardized protocol before and one month after trial VFI of 68 patients with vocal fold atrophy (30) and atrophy with sulcus (38) were analyzed. Voice Handicap Index (VHI)-30 was compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…16 Type 1 thyroplasty requires a percutaneous incision and is more invasive than vocal fold injection. The injection of bFGF was simple and, as shown in Table I, [17][18][19] satisfactory improvement was observed even when compared with other injections.…”
Section: Discussionmentioning
confidence: 93%
“…16 Type 1 thyroplasty requires a percutaneous incision and is more invasive than vocal fold injection. The injection of bFGF was simple and, as shown in Table I, [17][18][19] satisfactory improvement was observed even when compared with other injections.…”
Section: Discussionmentioning
confidence: 93%
“…In this study we used different subjective voice parameters, and in line with our study on trial vocal fold injection, we noticed only a partial overlap in these subjective voice parameters. 22 Therefor the question remains if the Voice Handicap Index, the main outcome measurement instrument used in this study, is valid and precise enough for this specific population of patients and what outcome measurement instrument would be the best alternative. We therefore again stress the need for further research on the most appropriate voice-outcome measurement instruments in this group of patients.…”
Section: Discussionmentioning
confidence: 98%
“…Woo and Murray found that platelet-rich plasma injection laryngoplasty improved voice quality temporarily, stroboscopic findings, and objective voice analysis outcomes in patients with vocal fold scar, sulcus and atrophy [39]. Similarly, Van den Broek et al showed a statistical, clinical and subjective improvement in voice and scores after bilateral injection laryngoplasty with hyaluronic acid in patients with vocal fold atrophy and sulcus vocalis [40]. Interestingly, they found the VHI-30 score obtained after the vocal fold injection to be a predictive value of the VHI-30 score outcome after a long-lasting medialization procedure.…”
Section: Treatmentmentioning
confidence: 93%